Teaching English Language Vocabulary to ESL Learners via mobile phone applications short message service (SMS): An Investigation Based on Arabic-speaking Learners - Abdou, Ali (2014)
Vocabulary is the corner stone in learning English language that affects the four skills of the language (reading listening, speaking and writing). Accordingly, this dissertation investigates students’ low achievement in learning second language vocabulary and how to improve their attainment by assimilating teaching, learning and technology in a model of partnering pedagogy. The study focuses on EFL male students in one of Dubai’s secondary schools aged 16:19. The diffusion of mobile phones all over the world is continually increasing , this dissertation applies mobile phones applications SMS in teaching and learning EFL vocabulary due to its comparatively low cost, quite use, asynchronous nature, and features of privacy . The study used the mixed approach (qualitative and quantitative) to investigate the effectiveness of using SMS applications on learning English vocabulary. Fifty students of grade 12 in Hamdan Bin Rashid for Secondary Education were the subjects of the study. Twenty five students in the control group studied academic vocabulary list of 60 words as a printed material. The other 25 students forming the experimental group studied the same 60 academic words via mobile phone applications (SMS). An analysis of the result showed no significant difference between both groups in the immediate post-test while there was a significant difference in the delayed post-test which signifies the effectiveness of using mobile phone applications in teaching and learning English vocabulary.